Design of the PRESTO Multimedia Storage Network (Extended Abstract) - Berenbrink, Petra; Riedel, Marco; Scheideler, Christian (International Workshop on Communication and Data Management in Large Networks (CDMLarge))

Kleiner Antrieb, große Wirkung - Zimmer, Detmar (Der Konstrukteur - Magazin für Konstruktion und Entwicklung (ASB))

Der Einfluss von Steuern auf Investitionsentscheidungen bei Unsicherheit - Sureth-Sloane, Caren

From Static to Dynamic Routing: Efficient Transformations of Store-and-Forward Protocols - Scheideler, Christian; Vöcking, Berthold (STOC)

Informatik '99: Informatik überwindet Grenzen. Tagungsband der 29. Jahrestagung der Gesellschaft für Informatik, Paderborn (Germany)

Patterns as a Means for Intelligent Software Engineering - Deugo, Dwight; Küster, Jochen; Oppacher, Franz; von Otte, Ingo (Proceedings of the conference on Artificial Intelligence (IC-AI 1999) Las Vegas, Nevada (USA))

Tile Transition Systems as Structured Coalgebras - Corradini, Andrea; Heckel, Reiko; Montanari, Ugo (Proceedings of the 12th International Symposium on Fundamentals of Computation Theory (FCT '99))

Application of the Structured Analysis and Design Technique (SADT) Methodology for the Medical Information Systems Development - Cherchago, Alexey (Proceedings of the All-Russia Students’, Young Scientists’ and Specialists’ Scientific and Technical Conference "New Information Technologies in Scientific Researches and in Education" (Ryazan, Russia))

Konzeption und objektorientierte Realisierung einer internet-basierten Datenbankanwendung - Engels, Gregor; Depke, Ralph; Borowski, Christoph (Kolloquium Software-Entwicklung - Methoden, Werkzeuge, Erfahrungen)
Today e-commerce applications use web browsers as an uniform user interface and they rely on databases as data sources. Different technologies exist for database access: common gateway interface (CGI), Java and its database interface java database connectivity (JDBC), proprietary approaches of database vendors, etc. We present criteria for the selection of an appropriate solution and we successivly apply them in our application development process. Throughout the development process of internet based database applications object oriented techniques can be used. The unified modeling language (UML) is used for requirement analysis and design of the application and the implementation proceeds with the programming language Java. The transition from the object oriented modeling language UML to the object oriented programming language Java succeeds smoothly. We report on our experience with the modeling tool Rational Rose 98 of Rational, Inc. We use Java and JDBC to implement a seminar reservation system that can be regarded as a small e-commerce application.

UML Collaboration Diagrams and Their Transformation to Java - Engels, Gregor; Hücking, Roland; Sauer, Stefan; Wagner, Annika (Proceddings of The Unified Modeling Language: Beyond the Standard, Second International Conference (UML 99), Fort Collins, Colorado, USA)